ASSESSMENT OF SAFETY AND FEASIBILITY OF ROTATIONAL ATHERECTOMY (RA) VERSUS CONVENTIONAL STENTING IN PATIENTS WITH CHRONIC TOTAL OCCLUSION (CTO) LESIONS - SHAH , SB; AHMED , S; KHAN , MU; KHAN , SK; ALRASHED , RFF (Biological and Clinical Sciences Research Journal, 2024)
Chronic total occlusion (CTO) sores in coronary arteries present a challenge in percutaneous coronary intervention (PCI) because of their complex anatomy and high rates of procedural failure. Objectives: In this comparative study, we aim to investigate the safety and feasibility of rotational atherectomy (RA) versus conventional stenting in patients with chronic total occlusion (CTO) lesions. Methods: This comparative study was conducted at Ayub teaching hospital from September 2023 to December 2023. Data was collected from 110 patients from both genders. Patients aged > 18 years and diagnosed with chronic total occlusion (CTO) lesions in coronary arteries confirmed by coronary angiography were included in the study. Baseline demographic and clinical data, including age, gender, comorbidities, and angiographic characteristics, were collected for each participant. Additionally, procedural details such as the type of intervention, rotational atherectomy, conventional stenting, procedural time, fluoroscopy time, contrast volume, and any adverse events encountered during the procedure were recorded. Results: Data were collected from 110 patients from both genders. The mean age of participants in the Rotational Atherectomy (RA) group was 62.4 ± 7.3 years, while in the Conventional Stenting group, it was 61.8 ± 6.9 years. There were 40 males and 15 females in the RA group, compared to 38 males and 17 females in the Conventional Stenting group. The prevalence of diabetes mellitus was 42.0% in the RA group and 45.5% in the Conventional Stenting group. Left ventricular ejection fraction (LVEF) was 53.7 ± 4.2% in the RA group and 54.1 ± 4.5% in the Conventional Stenting group. The RA group showed a success rate of 81.8%, and the conventional stenting group achieved a success rate of 90.9%. However, the RA group experienced slightly higher rates of major procedural complications (9.1% vs. 5.5%) and minor procedural complications (12.7% vs. 10.9%) than the conventional stenting group. Conventional stenting group, the mean change was -1.2 ± 0.7. Additionally, the incidence of target lesion revascularisation (TLR) was observed in 8 patients (14.5%) in the RA group and 12 patients (21.8%) in the conventional stenting group. Furthermore, major adverse cardiovascular events (MACE) occurred in 9 patients (16.4%) in the RA group and 11 patients (20.0%) in the conventional stenting group. Conclusion: It is concluded that both rotational atherectomy (RA) and conventional stenting are effective and safe treatment options for patients with chronic total occlusion (CTO) lesions. Our findings suggest that both strategies yield comparable procedural success rates, complication rates, and efficacy outcomes, including myocardial infarction frequency, troponin levels, and left ventricular ejection fraction changes.